2022
DOI: 10.1128/jb.00540-21
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Damage Reveals Spatial Flexibility in Peptidoglycan Synthesis and a Nonredundant Role for RodA in Mycobacteria

Abstract: Peptidoglycan synthesis is a highly successful target for antibiotics. The pathway has been extensively studied in model organisms under laboratory-optimized conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…6A). However, as with RodA absence or moenomycin treatment (Melzer et al, 2022) there was a modest but statistically significant decrease in the polarity of nascent peptidoglycan in Δ ponA2 compared to wild-type (Fig. 6B and 6C).…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…6A). However, as with RodA absence or moenomycin treatment (Melzer et al, 2022) there was a modest but statistically significant decrease in the polarity of nascent peptidoglycan in Δ ponA2 compared to wild-type (Fig. 6B and 6C).…”
Section: Resultsmentioning
confidence: 69%
“…We wondered whether PonA2 supports membrane homeostasis by localizing cell wall assembly. Previously we showed that the polarity of peptidoglycan synthesis decreases in the absence of RodA, a SEDS family transglycosylase (and upon treatment with moenomycin, an antibiotic that specifically inhibits transglycosylation of class A PBPs (aPBPs) such as PonA2 (Melzer et al, 2022). To more directly assay the function of PonA2, we labeled nascent peptidoglycan in wild-type and Δ ponA2 after a brief incubation in the presence of alkyne-D-alanine-D-alanine (alkDADA, also called EDA-DA (García-Heredia et al, 2018; Liechti et al, 2014)) and detected the presence of the alkyne probe via copper-catalyzed alkyne-azide cycloaddition (CuAAC) to a fluorescent azide label.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations